Program Pendampingan Penulisan Akademik Berbasis Mindfulness untuk Meningkatkan Profesionalisme dan Kesejahteraan Guru Sekolah Indonesia di Jeddah - Mintarsih Arbarini; Wulan Aulia Azizah; Yudi Siswanto; Indri Ajeng Setyoningrum; Rendi Agung Febrianto (Pusat Riset dan Inovasi Nasional, 2026)
Teacher professional development demands not only improvements in pedagogical and academic competence but also attention to psychological well-being, particularly in the context of academic writing, which often triggers stress and anxiety. Indonesian School Jeddah (SIJ) teachers face dual challenges: professional demands and limited formal academic writing training, alongside emotional pressure when completing writing tasks. This community service activity aims to enhance teacher professionalism and well-being through the Mindfulness-Based Writing Assistance program, which integrates mindfulness practices with process-based academic writing training. The activity involved 22 teachers through three main stages: preparation, implementation, and evaluation. Data collection instruments included evaluation questionnaires, structured observations, writing document analysis, and participants' narrative reflections. Data were analyzed using descriptive statistics and thematic analysis. Results showed that 84% of teachers experienced a reduction in writing stress, 88% showed increased focus, and 79% felt more confident in writing scientific papers. Additionally, document analysis revealed improvements in writing quality, specifically in understanding the IMRAD structure, paragraph coherence, reference usage, and argument strength. Narrative reflections disclosed increased self-awareness, courage to write, and motivation to continue independent scientific writing. These findings indicate that a mindfulness-based approach is effective in supporting teacher professional development while improving psychological well-being. This program contributes to the achievement of Sustainable Development Goals (SDGs) 3 regarding healthy lives and well-being, as well as SDGs 4 on quality education, and has the potential to be replicated in other Indonesian school contexts.